VERIFIKASI LINIERITAS KURVA BAKU TESTOSTERON MENGGUNAKAN METODE ELISA (ENZYME-LINKED IMMUNOSORBENT ASSAY) - Muhammad Arif Hanny Ferry Fernanda; Ashon Sa’adi; Sudjarwo (2477 - 6165, 2019)
Enzyme-Linked Immunosorbent Assay (ELISA) is one of the quantitative analysis methods that is often used to determine the levels of active compounds in biological samples. In this study we will verify the method of determining testosterone active compounds in blood and urine samples of female patients who have Polycystic Ovary Syndrome (PCOS) using the Human Testosterone ELISA Kit. Before conducting testosterone levels using ELISA, it is necessary to verify the linearity of the standard curve first to determine the effect of testosterone standard levels on the analyte response in the form of optical density. The linearity verification of the standard testosterone curve was calculated using linear regression calculations with determinant coefficient result was 0.978 and a value of α = 0.05. While for testing by using 4 parameter logistic (4PL) coefficient created, 0.999. Based on these results it can be concluded that the testosterone standard level has a significant influence on the response of optical density analytes.